2018
DOI: 10.1016/j.jff.2018.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a vinegar-based multi-micronutrient supplement in rats: A multi-pronged assessment of dietary impact

Abstract: We determined the effects of continuous access to drinking of water with a vinegar-based multi-micronutrient (VMm) supplement containing rice and fruit vinegars, vitamins, organic acids and sugars during gestation, lactation, and early adulthood in rats. Pregnant rats were provided with reverse-osmosis water or VMm water from the start of pregnancy through the time of weaning. Weaned pups consumed the same drinking water for 3–12 additional weeks. We examined fecal metabolite and microbial profiles, and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Metabolic pathway analysis revealed significant alterations in tryptophan metabolism in the vinegar group relative to controls. In rats, metabolomics analysis of urine also identified a change in tryptophan metabolism in the vinegar treated animals in comparison to controls [12]. These data are intriguing given the antioxidant role of indole-3-acetic acid in biological systems, including brain, and the well-documented role of tryptophan in production of the stress-alleviating neurotransmitter serotonin [13][14][15].…”
Section: Introductionmentioning
confidence: 84%
“…Metabolic pathway analysis revealed significant alterations in tryptophan metabolism in the vinegar group relative to controls. In rats, metabolomics analysis of urine also identified a change in tryptophan metabolism in the vinegar treated animals in comparison to controls [12]. These data are intriguing given the antioxidant role of indole-3-acetic acid in biological systems, including brain, and the well-documented role of tryptophan in production of the stress-alleviating neurotransmitter serotonin [13][14][15].…”
Section: Introductionmentioning
confidence: 84%
“…In addition, the disruption of the gut epithelium might be associated with the elevated lipopolysaccharide (LPS) level [33]. The previous results have shown that chemotherapy-associated gastrointestinal toxicity is related to the increased relative abundance of LPS-producing bacteria [34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the disruption of the gut epithelium might be linked to the elevated lipopolysaccharide (LPS) levels [ 27 ]. For example, it has been reported that chemotherapy-associated gastrointestinal toxicity might be related to the abundance of the LPS-producing bacteria [ 28 ]. It is plausible that both Bact A and Bact B could disturb the growth of such harmful bacteria in the gut.…”
Section: Discussionmentioning
confidence: 99%